The Unintended Consequences of “Ban the Box”: Statistical Discrimination and Employment Outcomes When Criminal Histories Are Hidden - Doleac, Jennifer L.; Hansen, Benjamin (Journal of Labor Economics, 2020)
Jurisdictions across the United States have adopted “ban the box” (BTB) policies preventing employers from asking about job applicants’ criminal records until late in the hiring process. Their goal is to improve employment outcomes for those with criminal records, with a secondary goal of reducing racial disparities in employment. However, removing criminal history information could increase statistical discrimination against demographic groups that include more ex-offenders. We use variation in the timing of BTB policies to test BTB’s effects on employment. We find that BTB policies decrease the probability of employment by 3.4 percentage points (5.1%) for young, low-skilled black men.